1997
DOI: 10.1002/(sici)1097-4644(19971101)67:2<275::aid-jcb13>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Novel nuclear matrix protein HET binds to and influences activity of the HSP27 promoter in human breast cancer cells

Abstract: Since the small heat shock protein hsp27 enhances both growth and drug resistance in breast cancer cells, and is a bad prognostic factor in certain subsets of breast cancer patients, we have characterized the transcriptional regulation of hsp27, with the long-term goal of targeting its expression clinically. The majority of the promoter activity resides in the most proximal 200 bp. This region contains an imperfect estrogen response element (ERE) that is separated by a 13-bp spacer that contains a TATA box. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 32 publications
1
44
1
1
Order By: Relevance
“…We first confirmed that RFP functions as a transcriptional repressor [22]; however, we were unable to detect any synergistic interaction between SAFB1 and RFP in heterologous transient transfections using expression constructs for Gal4 DNA-binding domain (DBD) fusion proteins and a UAS-TK-Luciferase reporter [8] (data not shown). Likewise, we could not shown an RFP effect on SAFB1-mediated ESR1 corepression [29].…”
Section: Rfp Does Not Enhance Safb1-mediated Repressioncontrasting
confidence: 73%
“…We first confirmed that RFP functions as a transcriptional repressor [22]; however, we were unable to detect any synergistic interaction between SAFB1 and RFP in heterologous transient transfections using expression constructs for Gal4 DNA-binding domain (DBD) fusion proteins and a UAS-TK-Luciferase reporter [8] (data not shown). Likewise, we could not shown an RFP effect on SAFB1-mediated ESR1 corepression [29].…”
Section: Rfp Does Not Enhance Safb1-mediated Repressioncontrasting
confidence: 73%
“…However, gene expression was not correlated with transgene copy number, suggesting that, although these promoter fragments contain tissue-specific cis-DNA regulatory elements, they may lack important elements such as matrix attachment regions or locus control regions. Matrix attachment regions are believed to facilitate gene expression and may serve as specific sequence landmarks as they anchor DNA to the nuclear scaffold (32)(33)(34). On the other hand, locus control regions are strong enhancers that bind multiple transcription factors that function in a cooperative manner (for review, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, locus control regions are strong enhancers that bind multiple transcription factors that function in a cooperative manner (for review, see Ref. 34). Both of these DNA elements are believed …”
Section: Discussionmentioning
confidence: 99%
“…We utilized two HSP27 promoter/luciferase reporter constructs (as described earlier by Oesterreich et al, 1997) to determine if exogenous BRCA1 is capable of activating the HSP27 promoter. In transient transfection assays using promoter constructs containing 15-1090 bp and 15-722 bp upstream of the transcription start site of human HSP27, exogenous wtBRCA1 induced (2.1 to 4.1)-fold increases in HSP27-Luc activity in both DU-145 prostate cancer and T47D breast cancer cells (Po0.001) (see Figure 6a).…”
Section: Exogenous Brca1 Activates the Hsp27 Promotermentioning
confidence: 99%